Effects of dietary waterlily (Nymphaea pubescens) stamen extract on growth performance and intestinal morphology of common lowland frog (Rana rugulosa) - Kamatit, Wannapa; Aoki, Supannee; Munglue, Phukphon (Asia-Pacific Journal of Science and Technology, 2016)
The effects of diets containing various levels (0, 1, 3 and 5%) of waterlily (Nymphaea pubescens) stamen extract (NPSE) on growth performance and intestinal morphology were investigated in common lowland frog (Rana rugulosa) with an initial weight of 16.09±0.50 g. After 11 weeks of feeding, growth parameters were evaluated. The results showed that the frogs fed with diets supplemented with 3 and 5% of NPSE exhibited significantly higher weight gain, specific growth rate and feed conversion ratio than frogs fed diets supplemented with 0 and 1% of NPSE (P<0.05). Significant differences were not observed in survival rate, hepatosomatic index and intestinosomatic index among the all diet groups (P>0.05). Villi heights, villi widths and the thickness of intestinal muscle layers in posterior intestine were significantly increased in frogs fed the diets containing NPSE (P<0.05). Observations on histology of anterior intestine found a significant increase in villi heights and circular muscularis thickness in the treated groups compared to the control group (P<0.05). However, villi widths and longitudinal muscularis thickness of anterior intestine did not affect by dietary treatment (P>0.05). Feeding behavior and feed acceptability of the experimental groups were the same as the control group. The optimal levels of NPSE observed in this present study were ranged between 3-5%. Our findings suggest that NPSE can be applied in the diets as a growth promoter in common lowland frog.